TO UNDERSTAND THE OTHER: THE VIETNAMESE CULTURE CODE - S. E. Glazunova (Концепт: философия, религия, культура, 2019)
Understanding the other is a prerequisite for full-ﬂedged communication and successful interaction with him, establishing trusting relationships in the process of negotiations or joint activities. Successful intercultural communication presupposes the willingness of participants to perceive, understand and accept stereotypes of behavior, customs, traditions, interests and cultural values of another ethno-cultural community. To achieve this, it is not enough to know the language of your dialogue partner; you need a deep understanding of the semantic content of various signs and symbols that arise in the process of knowing the other side, the cultural code as the key to understanding this culture. Vietnam is a country in Southeast Asia, on the one hand, historically related with the Soviet Union and therefore is known to us. On the other hand, in reality, the knowledge of the majority about this country is limited and superfcial. And despite the constant friendly relations between our countries, the practical content of our cooperation quite often does not meet expectations. The author of the article considers that in order to make the communication with Vietnamese partners more eﬀective, it is necessary to pay more attention to such aspects that at a frst glance seem far from politics and economics – traditions, customs, that cultural basis of Vietnamese society, which largely determines the model of behavior and reactions of its representatives. The basis of the worldview of the Vietnamese is the cult of ancestors. Even nowadays, it largely determines people’s moral and cultural values; it is the main “cipher” of the Vietnamese nation. But the cultural code permeates almost all areas of society. One of the most striking examples is cinema as the most popular art, as a sociocultural phenomenon, consistently reﬂecting the state of society. Historical and cultural allusions are also often traced in theatrical art. And if we talk about the cultural code, then, of course, frst of all it is a traditional theater, in particular, the Vietnamese theater “cheo”.